2010
DOI: 10.1017/s0007114510000498
|View full text |Cite
|
Sign up to set email alerts
|

Total body water and fat-free mass: evaluation of equations based on bioelectrical impedance analysis in infants and young children in India

Abstract: The association of early postnatal growth with diseases in adults such as hypertension, type 2 diabetes and CHD has generated interest in studying postnatal growth. Bioelectrical impedance analysis (BIA) is a useful measure to estimate total body water (TBW) and fat-free mass (FFM). We evaluated three published equations (Fjeld et al. (Pediatr Res (1990) 27, 98 -102), Bocage (MSc Thesis (1988) University of West Indies) and Kushner et al. (Am J Clin Nutr (1992) 56, 835 -839) to measure TBW and derived FFM ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 27 publications
(70 reference statements)
0
14
0
Order By: Relevance
“…For these and other reasons, BIA body composition equations tend to have poor performance across different ethnic groups and populations (Dehghan and Merchant, 2008), including in infants (Tanabe et al, 2012). For instance, FM and percent FM from total body electrical conductivity (TOBEC), a whole-body variant of BIA no longer commercially available (Hashimoto et al, 2002), and from BIA using existing equations (Sen et al, 2010) had poor correlation with estimates from isotope dilution. In both preterm (Dung et al, 2007) and term (Hashimoto et al, 2002; Lingwood et al, 2012) infants, BIA improves the prediction of FFM and percent body fat only very slightly, if at all, beyond simple anthropometrics (weight and length).…”
Section: Bioelectrical Impedance Analysis (Bia)mentioning
confidence: 99%
“…For these and other reasons, BIA body composition equations tend to have poor performance across different ethnic groups and populations (Dehghan and Merchant, 2008), including in infants (Tanabe et al, 2012). For instance, FM and percent FM from total body electrical conductivity (TOBEC), a whole-body variant of BIA no longer commercially available (Hashimoto et al, 2002), and from BIA using existing equations (Sen et al, 2010) had poor correlation with estimates from isotope dilution. In both preterm (Dung et al, 2007) and term (Hashimoto et al, 2002; Lingwood et al, 2012) infants, BIA improves the prediction of FFM and percent body fat only very slightly, if at all, beyond simple anthropometrics (weight and length).…”
Section: Bioelectrical Impedance Analysis (Bia)mentioning
confidence: 99%
“…One study, by Kushner et al, 17 involved pooled data from four varying datasets, thus the age of participants included ranged from birth to 67 years. Among other notable characteristics, four studies included preterm infants, [18][19][20][21] five included participants with varying levels of malnutrition, [22][23][24][25][26] and three included predominantly term infants. [27][28][29]…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Seven used a SFBIA device, [17][18][19][20][21]25,26 five studies used a device capable of multi-frequencies, [22][23][24]29,30 and three studies used a device capable of spectroscopy. 27,28,31 However, among the studies which used MFBIA or BIS, most used data obtained at a single frequency (50 kHz) in their analyses.…”
Section: Bia Devicesmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, the trunk has only a small contribution to whole body impedance (Fuller et al, 2002) and will be insensitive to fluid changes (Woodrow et al, 1996). Numerous studies have reported large discrepancies between BIA and TBWdil in children (Sen et al, 2010;Bell et al, 2013;Montugnese et al, 2013).…”
Section: Introductionmentioning
confidence: 99%